2013
DOI: 10.1097/aln.0b013e3182a05bb8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Plateau Pressure and Stress Index to Identify Injurious Ventilation in Patients with Acute Respiratory Distress Syndrome

Abstract: The best threshold values for discriminating morphological indexes associated with injurious ventilation were Pplat,Rs greater than 25 cm H(2)O and STRESS INDEX,RS greater than 1.05. Although a substantial discrepancy between Pplat,Rs and PPLAT,L occurs, STRESS INDEX,RS reflects STRESS INDEX,L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 48 publications
1
58
0
2
Order By: Relevance
“…5,6 Some studies have reported regional overdistention even with P plat Ͻ30 cm H 2 O, suggesting that there might not be a safe P plat . 7,8 Thus, the lungs should be ventilated with P plat as low as possible. Moreover, there is evidence supporting the use of a V T of 6 mL/kg predicted body weight in all mechanically ventilated patients and suggesting that large V T might contribute to the development of ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Some studies have reported regional overdistention even with P plat Ͻ30 cm H 2 O, suggesting that there might not be a safe P plat . 7,8 Thus, the lungs should be ventilated with P plat as low as possible. Moreover, there is evidence supporting the use of a V T of 6 mL/kg predicted body weight in all mechanically ventilated patients and suggesting that large V T might contribute to the development of ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a recent study using computed tomography to identify over-distention reported that injurious ventilation was associated with a P plat of Ͼ 25 cm H 2 O and a stress index of Ͼ 1.05. 6 …”
Section: Stress Indexmentioning
confidence: 99%
“…P plat should ideally be kept at Յ 30 cm H 2 O, 5 with some evidence suggesting that P plat should be targeted to Ͻ 25 cm H 2 O in patients with ARDS. 6,7 This assumes that chest-wall compliance (C CW ) is normal. A high P plat may be safe (and necessary) if C CW is decreased.…”
Section: Plateau Pressurementioning
confidence: 99%
“…Terragni et al assessed the accuracy of plateau pressure and stress index to identify the point associated with injurious ventilation. This study demonstrated that plateau pressure (Pplat) more than 25 cm H 2 O and stress index more than 1.05 have been shown the best performance to define the injurious ventilation (50). In terms of lung strain, the reference value computed by the ventilator is still controversial.…”
Section: Respiratory Mechanics and Esophageal Pressure Measurementmentioning
confidence: 99%